A GLANCE TO THE STORY OF GOOD MANUFACTURING PRACTICES FOR PHARMACEUTICALS - Jameela Helen Jacobs; Margret Chandira R; Deepu S; Benny KJ (Journal of Biomedical and Pharmaceutical Research, 2020)
Good Manufacturing Process (GMP) is the magic key that opens the door of quality. GMP is an evergrowing process as the new drugs are discovering day by day, but the concept is not new; its roots are very old. Everyone in our industry should know the story of how the GMP has come to be. Most requirements were put in place as a result of tragic circumstances and to prevent future tragedies. These regulations are mandatory for drug manufacturing companies in order to manufacture quality products. Keywords: GMP, FDA, WHO